Exploring the Thermal Signature of Guilt, Shame, and Remorse - Bhushan, Braj; Basu, Sabnam; Panigrahi, Pradipta Kumar; Dutta, Sourav (Frontiers in Psychology, 2020)
The recent study of complex emotions using visual storyboards by Bhushan et al. (2020) endorse that same scenario can induce guilt/remorse or guilt/shame in people based on valence. These findings were based on behavioural data and did not consider body physiology. The present study aimed to explore the difference in the thermal signature of scenarios which elicit guilt in some and shame/remorse in others. Using storyboard depicting 13 scenarios, we analyzed the thermal changes on the forehead, eyes (left and right separately), cheek (left and right separately), nose tip, and mouth regions of the face with the objective to explore the thermal signature of guilt, shame, and remorse. Data was collected from 31 participants using a thermal camera in a laboratory setting. We found a difference of 0.5°C or above change in temperature on the forehead, left and right cheeks, and mouth regions during guilt experience compared to shame and remorse experiences. The temperature of the right and left cheeks was high for guilt as compared to remorse for two scenarios inducing guilt/remorse and the difference was statistically significant. For one of the scenarios inducing guilt/shame, thermal change in the right eye region was higher for shame as compared to guilt. The findings are discussed in light of the distribution of blood vessels on the face.